Tailored photocatalysts and revealed reaction pathways for photodegradation of polycyclic aromatic hydrocarbons (PAHs) in water, soil and other sources - Van Huy Nguyen (2020)
© 2020 Elsevier Ltd Polycyclic aromatic hydrocarbons (PAHs), which are in the class of persistent organic pollutants, are considered as hazardous pollutants. To date, these compounds were detected globally in soil, sludge, water, and other contamination sources. A variety of treatment methods have been used in recent years to degrade PAHs in the environment. Photocatalysis, among advanced techniques, is proposed as the most effective method for the treatment of PAHs. In this context, we introduce the classification of PAHs, summarize, and highlight the recent studies on photodegradation of various types of PAHs. A series of efficient photocatalysts, including TiO2-, Ag3PO4-, ZnO-, MHCFs-based, and others, have been reported with the potential result for photodegradation of PAHs. Focus is also placed on revealing several possible reaction pathways for different types of PAHs that have been proposed in the literature. Particular attention to current status, challenges, and prospects in the future for enhanced photodegradation of PAHs are also discussed.